Multisystemic therapy project in Sweden: what factors affect the tendency of social workers to refer subjects to the research project? - Gustle, Lars-Henry; Hansson, Kjell; Sundell, Knut; Andrée-Löfholm, Cecilia (International journal of social welfare, 2007)
This article examines some of the factors that may have affected the tendency for social workers to refer adolescents to a randomised controlled study of multisystemic therapy (MST). If we are to improve integration between researchers and the clinical setting in the future, it is important to consider those factors that affect implementation of research projects and evidence‐based treatment methods. Evidence‐based methods that lack the support of clinicians will have problems surviving in clinical practice. In the present study, we found that social workers’ treatment ideology was associated with referral rate. Social workers who sympathised with the ideology on which MST is based referred patients to the project to a greater extent. Moreover, we found that the perception of a good work climate and good social support correlated positively with the referral rate from the unit. The results suggest that when implementing evidence‐based methods, or research projects on treatment methods, researchers should consider whether the method is consistent with the current treatment ideology within the unit. Working conditions in the unit should also be considered.